(untitled) (International Journal of Physiotherapy, 2014)
Background: The purpose is to find long term effect of Cyriax physiotherapy with supervised exercise program in the reduction of pain and improvement of functional ability for subjects with tennis elbow. Method: An experimental study design, 30 subjects with Tennis Elbow randomized 15 subjects each into Study and Control group. Control group received Supervised Exercise program while Study group received Cyriax Physiotherapy with Supervised exercises program thrice in a week for 4 weeks and post intervention follow up after 2 weeks. Outcome measurements were measured for pain using Visual analogue Scale (VAS) and Patient Rated Tennis Elbow Evaluation (PRTEE) for functional ability. Results: There is no statistically significant difference in pre- intervention means of VAS and PRTEE when compared between the groups using independent ‘t’ test as a parametric and Mann Whitney U test as a non-parametric test. When means of post intervention and follow-up measurements were compared there is a statistically significant (p<0.05) difference in VAS and PRTEE scores between the groups. However greater percentage of improvements was obtained in study group than control group. Conclusion: It is concluded that there is significant long term effect with greater percentage of improvement in pain and functional ability up to 2 weeks follow-up following 4 weeks of combined Cyriax physiotherapy with supervised exercise program than only supervised exercise program for subjects with tennis elbow.